NEW MODEL FOR LOCAL POST DISASTER TOURISM GOVERNANCE: Evidence from Indonesia’s Merapi Volcano - Muchamad Zaenuri (Magister Ilmu Administrasi Publik, 2021)
This article examines the dynamics of local post-disaster tourism governance in areas on the foothills of Merapi Volcano in Yogyakarta, Indonesia, which is one of the world’s most intensively active volcanoes. In this research, the author invites the readers to discuss the success achieved in local collaboration through transforming disaster life into a profitable tourism site. They face difficult situations amid government limitations in handling this post-disaster development. Using qualitative descriptive analysis, this study offers a new local-based collaboration model, especially for the post-disaster tourism governance in developing countries. Result of the study showed that local collaboration cannot be achieved in an instant, rather involves a process that is influenced by local wisdom. This article makes positive contribution to public policy literature and is essential for policymakers at the lower level and concerned about local-based development and empowerment